Early onset type 1 diabetes mellitus in an infant during COVID-19 pandemic: case report - Astiti, Made Yuliantari Dwi; Pramana, Putu Harrista Indra; Suryawan, I. Wayan Bikin (International Journal of Research in Medical Sciences, 2021)
Type 1 diabetes mellitus (T1DM) is an endocrine disorder, marked by elevated blood glucose level caused by autoimmune process destroying the β-cells of the pancreas which mostly affects children. It is an often-overlooked condition, with low awareness among clinicians and parents alike which led to late diagnosis and patients often presenting with acute complications. Often triggered by a viral infection, here we presented an interesting case of early onset T1DM presenting with Diabetic ketoacidosis (DKA) during a COVID-19 pandemic. A female infant, aged 1 years and 2 days old, presented with dyspnea and fever. Physical examination was otherwise normal, without any rhonchi or wheezing found during pulmonary auscultation. Nasopharyngeal swab and SARS-CoV-2 antigen test was found negative. Laboratory workup found random blood glucose level of 577 mg/dl accompanied by acidosis and ketonuria. The patient also had elevated white blood cells and platelet counts. She was admitted for treatment in the Pediatric intensive care unit (PICU) with therapeutic regiments consisting of slow intravenous insulin infusion, potassium chloride intravenous fluid, antibiotics, and antipyretics. Close monitoring of blood glucose ensues and the patient was treated for 5 days followed by outpatient therapy with mixed insulin treatment twice per day. This case was interesting as T1DM usually manifested in older children with median age of diagnosis ranging from 8 to 13 years old, depending on population. T1DM diagnosed in children younger than 6 years old are classified early onset and it is especially rare to found in infants. Although the patient tested negative for SARS-CoV-2 antigen, the onset of the case coincides with a recent surge of cases locally. It meant that we cannot rule out possibility of prior unknown exposure or infection which may precipitate the condition.